USE OF HYPERTEKS TO IMPROVE THE CAPNITIVE ASPECT ABILITY OF SCHOOL BASIC STUDENTS ON A SIMPLE AIRPORT SUPPORT - Ramdhan Witarsa; Irwan Medriana; Dina Medriana (PrimaryEdu : Journal of Primary Education, 2017)
The main issues of this research are how to improve the cognitive aspects of elementary school students on the subject of simple plane through the use of hypertext. The objectives of the research are as follows: (1). Improving cognitive aspects of elementary students through Hypertext; (2). Providing Hypertext learning through a fun and inspiring computer device can inspire elementary students. The methods / approaches used in achieving the following objectives: (a). Collect students and elementary teachers involved in research; (B). Provide an overview of the research activities to be undertaken; (C). Reflecting, discussing the use of hypertext; (D). Collaborate with elementary teachers in the determination of experimental class and control class; (E). Implementation of Hypertext Study; (F). Evaluation of Hypertext Learning. The results showed that there was an increase of cognitive aspect ability of elementary school students through Hiperteks by 33%; (2). Elementary students are enthusiastic with Hypertext lessons given by teachers; (3). Collaborative occurrence between one student and another student at the time of Hypertext learning is done.Keywords: Learning, Hypertext, Cognitive